Quality Management in Arabic Language Learning Integrating Technology and Islamic Values in the Society 5.0 Era - Azmi Islami; Busthomi Ibrohim; Agung Muttaqien; Agus Mujib (Universitas Darunnajah Jakarta, Indonesia, 2026)
The transition toward Society 5.0 has obliged Islamic educational institutions in Indonesia to reconsider how Arabic is planned, delivered, and evaluated. Although digital tools grow abundant every year, discussions about quality tend to stop at whether the technology functions, not whether it truly upholds the spiritual and pedagogical mission of Arabic as the language of the Qur'an. This article addresses that concern through a Systematic Literature Review (SLR) following the PRISMA 2020 protocol. Forty-two peer-reviewed articles published between 2020 and 2025 were selected from Scopus, DOAJ, and SINTA 1–2 indexed journals. Thematic synthesis yielded three interrelated findings: first, effective quality management rests on leadership that is digitally literate yet anchored in adab; second, technology integration succeeds when teachers are treated as co-designers rather than end-users; third, Islamic values work only when embedded in the structural decisions of the institution, not when treated as decorative additions. A conceptual framework that bridges total quality management, human-centered technology integration, and the integration of Islamic values into the curriculum is presented. The review contributes to the discourse on digital transformation in Islamic education and outlines priorities for empirical research in madrasah and pesantren settings.